2020
DOI: 10.1177/0956462419887042
|View full text |Cite
|
Sign up to set email alerts
|

Surveying testing preferences in Black, Latin American, and other minorities for the co-design of digital vending machines for HIV self-testing

Abstract: The use of digital vending machines (VMs) to delivery HIV self-testing (HIVST) could expand HIV testing in priority populations. We surveyed primarily Black African (BA) participants and other minority ethnicities, to identify acceptability, preferences, and concerns of using VMs for HIVST dispensing. A structured survey was developed with Black African and Caribbean, Latin American and other Minorities (BLAM) communities, and distributed between September 2018 and January 2019. Participants were recruited usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 15 publications
0
28
0
Order By: Relevance
“…The use of vending machines to dispense HIV self-test kits has been shown to be acceptable and feasible in increasing testing. Investigators have found that dispensing HIV self-test kits in vending machines was acceptable among MSM [ 63 ] and blacks/African American, Hispanic/Latino, and other minorities [ 64 ]. Placement of vending machines may be particularly key in reaching populations at most risk.…”
Section: Resultsmentioning
confidence: 99%
“…The use of vending machines to dispense HIV self-test kits has been shown to be acceptable and feasible in increasing testing. Investigators have found that dispensing HIV self-test kits in vending machines was acceptable among MSM [ 63 ] and blacks/African American, Hispanic/Latino, and other minorities [ 64 ]. Placement of vending machines may be particularly key in reaching populations at most risk.…”
Section: Resultsmentioning
confidence: 99%
“…The placement of an HIVST vending machine in the sexual health clinic waiting room was also found to be acceptable in a survey of 193 black, Latin American and other minority ethnic service users in London. 11 In summary, HIVST vending machines are an acceptable, innovative way to encourage HIV testing. Providers need to ensure this intervention is supported by adequate information regarding the limitation of the test and how to access comprehensive services to avoid any unintended negative effects.…”
Section: Discussionmentioning
confidence: 99%
“…The placement of an HIVST vending machine in the sexual health clinic waiting room was also found to be acceptable in a survey of 193 black, Latin American and other minority ethnic service users in London. 11…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations